PENGARUH REWARD DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 2 SIAK HULU - Muhammad Ade Novid Hardian; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the effect of rewards and the school environment on student learning outcomes at SMA Negeri 2 Siak Hulu. The population in this study was all class XI social studies students at SMA Negeri 2 Siak Hulu as many as 138 students and in this study used a proportional sample technique, namely the display of samples from several sub-populations with a proportional number. To determine the size or number of samples from the population using issac tables with an error rate of 10%. Based on the table with an error rate of 10%, if the population in this study was 138, then the sample was 92 students. Data was collected using questionnaires about rewards and school environment that were distributed to respondents. Data analysis using multiple linear regression test data analysis. Based on the results of the study, the effect of rewards and school environment on the learning outcomes of class XI social studies students in economics subjects at SMA Negeri 2 Siak Hulu was 0.231 or 23.1% while the remaining 76.9% was influenced by other factors that were not studied in this study such as physical factors, fatigue, family conditions, and society.Key Words: Reward, School Environment, Learning Outcomes.